An Electrochemical, Microtopographical and Ambient Pressure X-Ray Photoelectron Spectroscopic Investigation of Si/TiO2/Ni/Electrolyte Interfaces. Issue 2 (1st January 2016) - Lichterman, Michael F.; Richter, Matthias H.; Hu, Shu; Crumlin, Ethan J.; Axnanda, Stephanus; Favaro, Marco; Drisdell, Walter; Hussain, Zahid; Brunschwig, Bruce S.; Lewis, Nathan S.; Liu, Zhi; Lewerenz, Hans-Joachim
Abstract : The electrical and spectroscopic properties of the TiO2 /Ni protection layer system, which enables stabilization of otherwise corroding photoanodes, have been investigated in contact with electrolyte solutions by scanning-probe microscopy, electrochemistry and in-situ ambient pressure X-ray photoelectron spectroscopy (AP-XPS). Specifically, the energy-band relations of the p + -Si/ALD-TiO2 /Ni interface have been determined for a selected range of Ni thicknesses. AP-XPS measurements using tender X-rays were performed in a three-electrode electrochemical arrangement under potentiostatic control to obtain information from the semiconductor near-surface region, the electrochemical double layer (ECDL) and the electrolyte beyond the ECDL. The degree of conductivity depended on the chemical state of the Ni on the TiO2 surface. At low loadings of Ni, the Ni was present primarily as an oxide layer and the samples were not conductive, although the TiO2 XPS core levels nonetheless displayed behavior indicative of a metal-electrolyte junction. In contrast, as the Ni thickness increased, the Ni phase was primarily metallic and the electrochemical behavior became highly conductive, with the AP-XPS data indicative of a metal-electrolyte junction. Electrochemical and microtopographical methods have been employed to better define the nature of the TiO2 /Ni electrodes and to contextualize the AP-XPS results.